Challenges in Malaysian Design Industry: Managing Design and Decision-making Processes - Ali, Abu; Liem, Andre; Isa, Siti Salwa; Jamaludin, Nor Lelawati (FormAkademisk, 2024)
The Malaysian design industry follows a market-need-driven approach, where marketing-oriented managers guide designers to address anticipated high-demand markets. However, challenges persist in understanding designers' problem-solving approaches due to implicit practices. This research emphasizes the hindrance caused by insufficient communication and collaboration among managers, designers, and researchers, impeding a comprehensive grasp of innovation processes in the manufacturing sector. The paper advocates a pragmatic examination of designers' experiences, highlighting sensemaking, speculative imagination, and improvisation as crucial design activities. Results show Malaysian industrial designers face consistent challenges with management, impacting the development process. The study contributes to formulating a practical solution for fostering creativity among managers, designers, and stakeholders in the design industry.